Health advocacy and primary health care: evidence for nursing - Carla Aparecida Arena Ventura; Laís Fumincelli; Marcela Jussara Miwa; Mirella Castelhano Souza; Maria da Glória Miotto Wright; Isabel Amélia Costa Mendes (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to analyze nursing actions involving health advocacy in the context of primary health care and the consolidation of this right to health. Methods: this is an integrative literature review with content analysis of the results on health advocacy and its relationship with nursing in the context of primary health care. Results: the content analysis of the seven selected studies resulted in two thematic categories: "Right to health - a complex and progressive consolidation movement in Brazil" and "Advocacy in health and nursing". Conclusions: despite the difficulties in defining the concept of health advocacy, nurses, in their practice, act with innovative alternatives to daily conflicts, exercising the users' right to health in their relationships with health team members and the community.